Navigating Early Childhood Challenges: Teachers’ Approaches to Managing Behavioral, Emotional, and Developmental Differences in Young Learners - Wahyuni, Sry (Lembaga Penerbitan dan Publikasi Ilmiah Yayasan Pendidikan Tumpuan Bangsa, 2025)
Early childhood education represents a fundamental stage in shaping children’s cognitive, social, emotional, and language development. Then, this study aims to identify and analyze the challenges experienced by early childhood teachers in the learning process, particularly in foreign language instruction, as well as the strategies used to address these challenges. A qualitative approach was employed, using in-depth interviews with five early childhood teachers from five different schools in Makassar. The data were analyzed through a process of data reduction, data display, and conclusion drawing to gain their experiences, perceptions, and strategies in early childhood education. The findings reveal five major challenges in teaching practice: (1) difficulties in maintaining children’s focus and attention; (2) diverse abilities and characteristics among children; (3) the presence of children with special needs and the challenges related to supporting them; (4) difficulties in establishing emotional closeness; and (5) variations in children’s moods and learning readiness. Teachers addressed these challenges by implementing engaging activities, adapting learning materials, providing additional time for children with special needs, fostering warm interactions, and allowing children to calm themselves before rejoining learning activities. These findings are expected to offer important implications for the development of early childhood teacher training programs, particularly those focusing on behavior management, emotional support, and differentiated instruction.